2009
DOI: 10.1158/0008-5472.sabcs-6113
|View full text |Cite
|
Sign up to set email alerts
|

High-dose chemotherapy with autologous stem-cell support versus standard-dose chemotherapy: meta-analysis of individual patient data from 6 randomized metastatic breast cancer trials.

Abstract: #6113 Background: The role of high-dose chemotherapy (HDC) with autologous hematopoietic stem-cell transplantation for metastatic breast cancer has not been well defined. The statistical power of the available trials has limited precision for determining whether HDC has any benefit for this indication, or for any subset of patients.
 Methods: Individual patient data from the 6 known randomized trials were merged into a single database. The primary endpoint was overall survival (OS): t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…The role of auto-HSCT for primary BC at high risk of recurrence (at least four involved axillary lymph nodes) has been assessed by several randomized trials, 167 recently evaluated by a meta-analysis of individual patient data. 168 Overall, it was shown that high-dose therapy prolonged disease-free survival when used as adjuvant therapy, and showed a benefit on BC-specific survival and OS in selected cohorts of patients. 169,170 Whether auto-HSCT has benefit in the context of contemporary taxane-based regimens and targeted therapies is largely unknown.…”
Section: Breast Cancer (Bc)mentioning
confidence: 97%
“…The role of auto-HSCT for primary BC at high risk of recurrence (at least four involved axillary lymph nodes) has been assessed by several randomized trials, 167 recently evaluated by a meta-analysis of individual patient data. 168 Overall, it was shown that high-dose therapy prolonged disease-free survival when used as adjuvant therapy, and showed a benefit on BC-specific survival and OS in selected cohorts of patients. 169,170 Whether auto-HSCT has benefit in the context of contemporary taxane-based regimens and targeted therapies is largely unknown.…”
Section: Breast Cancer (Bc)mentioning
confidence: 97%
“…One trial, the PEGASE 04 study, showed a significant benefit in terms of both progression-free survival and overall survival (Table 8) [96]. In 2008, Berry et al [101] presented the first meta-analysis using individual data from six of the eight trials; this analysis showed a significant benefit in terms of progression-free survival and a trend toward benefit in terms of overall survival. Subgroup analysis suggested that young patients (less than 50 years old) and patients with only soft tissue involvement will benefit from this treatment.…”
Section: Microscopic Treatment In Metastatic Breast Cancermentioning
confidence: 99%
“…When looking at prospective randomized studies An equivalent or better EFS has been shown in all trials but, only one published as full report could demonstrate an OS advantage (11). A recent metaanalysis of phase III studies failed to demonstrate a survival advantage of HDC in MBC (23). Also for MBC it would be important to identify pts, if any, that are likely to benefit most from HDC.…”
Section: Metastatic Bcmentioning
confidence: 99%